Rethinking Southern African Higher Education: Handling Policy, Opening Doors, and Overcoming Obstacles - Pinias Chikuvadze; Joseph Zuva; Christopher Mutseekwa; Tabeth Nyarai Pazvakavambwa (Universitas Negeri Malang, 2025)
Abstract: Due to emerging socio-political conditions, economic competition, and global trends, higher education in Southern Africa has undergone significant changes recently. Nonetheless, several policy concerns continue to impede the expansion and advancement of higher education establishments in Southern Africa. In light of this, this paper aimed to comprehend the policy concerns plaguing Southern African higher education. In this sense, a qualitative approach is the foundation for data generation, analysis, and discussion. This enables it to search for participants' experiences and opinions in the higher education reform process. This encompasses policy analysis to interrogate 112 peer reviewed papers selected from the Scopus, DOAJ, DHTE, Scielo SA, and WoS and written. Hence, content analysis is required to identify themes and trends in this paper. This makes it possible to seek out the experience and views of the stakeholders within the reform process in the higher education. This entails policy analysis to examine the government and institutional policies, international publications and reports. The necessity of this paper is to utilise content analysis to establish themes and trends in higher education policy and reforms in Southern Africa. Although the interrogation of these questions in the case of Southern African nations like South Africa, Zambia, Zimbabwe, etc., the paper peaks top policy concerns in higher education, opening doors and overcoming obstacles of reform. From the above conclusion, a recommendation is made on sharpening the policy agenda in Southern Africa’s higher education. Keywords: Handling policy, higher education, rethinking, Southern Africa